Energy-saving technologies in design and construction of residential buildings and industrial facilities in the far North - Berseneva, M.; Vasilovskaya, G.; Danchenko, T.; Inzhutov, I.; Amelchugov, S.; Yakshina, A.; Danilovich, H. (2020)
The article discusses the main problems of energy saving and special features of design, construction and operation of residential buildings and industrial structures in extreme climatic conditions of the Northern territories. The impact of permafrost, seasonal thawing of soils and low bearing capacity of thawed soils on the choice of ways of arrangement of cities and pipelines in the Northern regions of Russia have been analyzed. There have been assessed the effect of climate change and the associated natural and man-made risks in the Far North on the development of a system of measures to ensure the reliability of energy facilities and options for emergency response. The solutions allowing to increase energy-saving capabilities of buildings and to reduce expenditures at their operation have been designated. Necessity of using non-traditional and renewable energy sources has been considered.